Rotary powers of various dialkyl-substituted esters of ℓ-menthol - Ritchie, James T. R. (The University of Edinburgh, 1931)
The chemical enquiry into the nature of optical activity has in the main been approached by selecting a particular molecular model, to which one or more asymmetric groups are attached, and determining the effect upon the rotatory power of introducing one or more substituents.